PEMBERDAYAAN MASYARAKAT BERBASIS KEWIRAUSAHAAN DI KAWASAN KAMPUNG MAKAM RANGKAH SURABAYA - Novaria, Rachmawati; Mulyati, Awin; Pujianto, Agung; Safitri, Lidya Alfianti (Jurnal Bisnis Indonesia, 2020)
The 'Tombs' village of Rangkah is one of the unique villages in the middle of the public cemetery in Rangkah, Surabaya. The problem in this tomb village is that teenagers still feel they lack the experience and skills for business provision. The entrepreneurial knowledge possessed by the residents is still lacking so they are less able to see profitable business opportunities to be developed in their villages. For this reason, entrepreneurship-based community empowerment activities are given so that they have an entrepreneurial spirit that is assisted by Untag Surabaya students where they try to practice their knowledge and help especially teenagers and children who cannot afford schooling are trained to be able to read and write English and empower their mothers who were originally unemployed can have a busy and entrepreneurial activity in the form of manufacturing processed foods that can improve their standard of living. And teenagers are given training to foster the spirit of entrepreneurship, their hopes are to increase the potential that exists in the tomb area of ​​Rangkah so that it is not only known as a tomb village. Keywords: Community Empowerment; Tomb village ;; Entrepreneurship   Kampung ‘Makam’ Rangkah merupakan salah satu kampung unik yang berada di tengah kawasan pemakaman umum Rangkah Kota Surabaya. Permasalahan yang ada di Kampung Makam ini para remaja  masih merasa kurang memliliki pengalaman dan ketrampilan untuk bekal usaha. Pengetahuan kewirausahaan yang dimiliki warga masih kurang sehingga mereka kurang mampu melihat perluang usaha yang menguntungkan untuk dikembangkan di kampungnya. Untuk itu kegiatan pemberdayaan masyarakat berbasis kewirausahaan diberikan agar mereka memiliki semangat kewirausahaan yang dibantu oleh mahasiswa Untag Surabaya dimana mereka mencoba mempraktekan ilmunya dan membantu terutama remaja dan anak-anak yang tidak mampu sekolah dilatih untuk bisa baca tulis bahasa inggris dan memberdayakan ibu-ibunya yang awalnya menganggur bisa memiliki kesibukan dan kegiatan kewirausahaan  berupa pembuatan makanan olahan yang dapat meningkatkan taraf hidupnya. Dan para remaja diberikan pelatihan untuk menumbuhkan semangat berwirausaha, harapannya untuk meningkatkan potensi yang ada di kawasan makam Rangkah agar tidak hanya terkenal sebagai kampung makam saja. Kata kunci:  Pemberdayaan masyarakat; Kampung makam;; Kewirausahaan